2012
DOI: 10.1186/1750-1172-7-42
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor I deficiency: a not so rare immune defect. Characterization of new mutations and the first large gene deletion

Abstract: BackgroundComplement Factor I (CFI) is a serine protease with an important role in complement alternative pathway regulation. Complete factor I deficiency is strongly associated with severe infections. Approximately 30 families with this deficiency have been described worldwide.Patients and methodsWe have studied five new Spanish families suffering from CFI deficiency. From 19 screened people, 7 homozygous, 10 heterozygous and 2 healthy subjects were identified. Clinical, biochemical and genetic descriptions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 34 publications
0
41
0
Order By: Relevance
“…In-frame deletions that respect the heptad pattern permit for formation of hybrid repeats, and triple coiling may occur. The alpha helix may form in fractional repeats, but triple coiling does not occur due to the absence of a heptad pattern 31. These differences in structure of mutant truncated dystrophin might account for the variability in the phenotypes of BMD and DMD.…”
Section: Discussionmentioning
confidence: 99%
“…In-frame deletions that respect the heptad pattern permit for formation of hybrid repeats, and triple coiling may occur. The alpha helix may form in fractional repeats, but triple coiling does not occur due to the absence of a heptad pattern 31. These differences in structure of mutant truncated dystrophin might account for the variability in the phenotypes of BMD and DMD.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the CFI mutations found in aHUS lead to impaired secretion or function [68, 69]. Recently, larger deletions containing all or part of CFI have also been described [70, 71]. …”
Section: Atypical Hemolytic Uremic Syndrome (Ahus)mentioning
confidence: 99%
“…30% of patients with factor I mutations also have mutations in other genes encoding complement-regulatory proteins [45] . Recent molecular studies demonstrated four novel mutations in a cohort of screened individuals; among them, the first major gene deletion in the CFI locus was described [76] .…”
Section: Factor I Mutationsmentioning
confidence: 99%